Brownian Tree‐Shaped Dendrites in Quasi‐2D Perovskite Films and Their Impact on Photovoltaic Performance. Issue 13 (6th February 2022) - Zheng, Fei; Angmo, Dechan; Hall, Christopher R.; Rubanov, Sergey; Yuan, Fangfang; Laird, Jamie S.; Gao, Mei; Smith, Trevor A.; Ghiggino, Kenneth P.
Abstract: Quasi‐2D Ruddlesden–Popper perovskites (RPPs) are candidates for constructing perovskite solar cells (PSCs) with superior stability due to their tolerance to the external environment. Fully understanding the film growth mechanism and structure is crucial to further improve the performance of 2D‐PSCs while maintaining device stability. In this work, the origin of Brownian tree‐shaped dendrites formed in hot‐cast methylammonium chloride (MACl)‐doped BA2 MA n −1 Pb n I3 n +1 (< n > = 5) quasi‐2D perovskite films are reported. Investigations based on optical, electronic, atomic force, and fluorescence microscopies reveal that the dendrites are assembled from large‐ n RPPs‐dominated grains, while the nondendritic film area is composed of small‐ n RPPs grains and associated with film surface pits caused by the evaporation of MACl. It is proposed that these dendrites are grown by the diffusion‐limited aggregation of the MA‐rich intermediate phase domains that initially crystallize from the precursor. The formation of these dendrites in quasi‐2D perovskite films upon MACl doping is accompanied by improved organization and crystallinity of the 2D RPPs, which benefits the photovoltaic performance. This work provides new insights into the formation mechanism of quasi‐2D perovskite films that should assist device engineering strategies to further improve the performance of 2D PSCs. Abstract : Brownian tree‐shaped dendrites present in quasi‐2D Ruddlesden–Popper perovskite films doped with methylammonium chloride (MACl) are grown by diffusion‐limited aggregation of the MA‐rich intermediate phase domains that initially crystallize from the precursor. The formation of these dendrites is accompanied by improved organization and crystallinity of the films, which leads to improved photovoltaic performance.